Ackonc-AWA: A multi-species animal welfare assessment protocol for wild animals under human care to overcome the use of generic welfare checklists - Racciatti, Débora Silvia; Feld, Alejandra; Rial, Laura Analía; Blanco, Carlos; Tallo-Parra, Oriol (Frontiers in Veterinary Science, 2022)
Maintaining a high level of animal welfare is essential in zoos, sanctuaries and aquaria for ethical, legislative and functional reasons. Therefore, it is necessary to have welfare assessment protocols that can be incorporated into daily management programs. Currently, there are different approaches to assessing animal welfare in zoos. Those that can be applied to multiple species consist of checklists or qualitative assessments, with limitations, especially regarding the lack of guidance in the selection and interpretation of indicators. Validated protocols also exist, but they are for very few wild species. This study aimed to develop, test on field and describe an animal welfare assessment protocol for wild animals under human care, that can be applied to multiple species, intended to overcome the use of generic welfare checklists and offer an alternative to challenging and time consuming species-specific tools. The development process consisted of the elaboration of a protocol, substantiated by published literature on zoo animal welfare and multidisciplinary focus group work, and its on-field feasibility test. This was performed on 14 species of different taxa housed in an Argentinian zoo. The protocol was structured in two forms: an initial form to serve as scan using various animal-based (ABM), resource-based (RBM) and management-based measurements (MBM), and a follow-up form using exclusively ABM. The protocol also included a user’s manual with information about preliminary preparation, equipment required, steps from arrival until completion, and details on how to assess each indicator. The scoring method consisted in rating each indicator on a 3-point scale. As a result, 23 ABM, 19 RBM, and three MBM were tested and selected to integrate Ackonc-AWA, a multidimensional protocol covering the five animal welfare domains and applicable to multiple species. This protocol was entirely developed in Spanish and can be applied noninvasively and at a low cost, which constitute features of high relevance for Latin America. Further applications of the described welfare assessment tool in other species and different institutional contexts will reinforce the validation of the proposed measurements and allow the systematic and routine evaluation of animal welfare in zoos.